Implementation of multiple linear regression to estimate profit on sales of screen printing equipment - Khairul Khairul; Asyahri Hadi Nasyuha; Ali Ikhwan; Moustafa H. Aly; Ahyanuardi Ahyanuardi (JURNAL INFOTEL, 2023)
Traditional marketing strategies are no longer practical to implement because the process requires more costs and time to disseminate information which is much longer. Data Mining is a science that discusses knowledge from previous data to estimate the amount of production in the future. Data mining is a term used to find hidden knowledge in databases. “Data mining is a semi-automatic process using statistical, mathematical, artificial intelligence, and machine learning techniques to extract and identify valuable and helpful information in large databases. It is necessary to solve the problem by using one of the five methods in the field of Data Mining, namely the Multiple Linear Regression method, where this method will analyze the variables that have an influence and can make estimates. Multiple Linear Regression Is a method that can be used to analyze data and obtain meaningful conclusions about a relationship between one variable and another. This relationship is generally expressed by a mathematical equation expressing the relationship between the independent and dependent variables in the form of a simple equation